The Role of Information Technology in Z Generation Behavior Change in Dealing with Conflict - Sumolang, Nortje (JR Education, 2023)
Developments in information technology such as the Internet, social media, and mobile devices have provided broad and immediate access to information and social interaction. However, the impact of information technology on the behavior of the Z Generation in dealing with the conflict still needs to be studied in depth. This study aims to explore the role of information technology in changing the behavior of the Z Generation in dealing with conflict. The Z Generation, which consists of individuals born between 1995 and 2010, grows and develops amidst the rapid advances in information technology. This study will use a qualitative approach by collecting data through in-depth interviews and participatory observation. Research participants will consist of Z Generation individuals who actively use information technology in their daily lives. This study will analyze the role of information technology in changing the behavior of the Z Generation in dealing with conflict, both in personal, social, and environmental contexts. Factors such as fast access to information, the influence of social media, and the ability to communicate virtually will be explored in relation to changes in the behavior of the Z Generation. It is hoped that the results of this research will provide better insight into how information technology influences the way Z Generation deals with conflict, as well as the implications of the change in behavior. The results of this research are expected to contribute to our understanding of how information technology can be used effectively in supporting the social and personal development of the Z Generation in dealing with conflicts in the digital era.